2022
DOI: 10.5812/jme-129450
|View full text |Cite
|
Sign up to set email alerts
|

Item Analysis of Multiple Choice and Extended Matching Questions in the Final MBBS Medicine and Therapeutics Examination

Abstract: Background: Most universities around the world use the multiple-choice question (MCQ) examination format to evaluate medical education. However, the suitability and advantages of traditional MCQs and extended matching questions (EMQs) continue to be debated. Objectives: This study mainly aimed to perform a comprehensive comparative analysis of the performance of the EMQ and traditional MCQ formats in the final MBBS exit examination. Methods: We conducted an item analysis of 80 EMQs, and 200 MCQs administered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…These questions assess students’ ability to integrate information, reflecting real-world challenges, and shaping competent professionals. 14–16 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These questions assess students’ ability to integrate information, reflecting real-world challenges, and shaping competent professionals. 14–16 …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Analyzing MCQs in medical education is crucial as it allows educators to assess the effectiveness of questions in testing higher-order thinking and clinical reasoning skills, ensuring assessments accurately reflect the skills required for medical practice. [14][15][16] While AI's capabilities in answering queries and simulating scenarios are noteworthy, the depth and breadth of its understanding, especially concerning multiplechoice questions (MCQs) of medical exams, still need to be thoroughly evaluated. 17 Several studies have demonstrated that ChatGPT outperforms medical students on MCQ items in board and licensing exams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation